2012
DOI: 10.1186/1471-2458-12-530
|View full text |Cite
|
Sign up to set email alerts
|

The development and validation of an urbanicity scale in a multi-country study

Abstract: BackgroundAlthough urban residence is consistently identified as one of the primary correlates of non-communicable disease in low- and middle-income countries, it is not clear why or how urban settings predispose individuals and populations to non-communicable disease (NCD), or how this relationship could be modified to slow the spread of NCD. The urban–rural dichotomy used in most population health research lacks the nuance and specificity necessary to understand the complex relationship between urbanicity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 13 publications
3
42
1
Order By: Relevance
“…The interrelation between SES and urbanicity is complex and beyond the scope of this study; however, directions of all associations observed are consistent with previous literature [11][16],[18],[40],[47]. Finally the generalisability of our results to other rural communities needs to be considered.…”
Section: Discussionsupporting
confidence: 82%
“…The interrelation between SES and urbanicity is complex and beyond the scope of this study; however, directions of all associations observed are consistent with previous literature [11][16],[18],[40],[47]. Finally the generalisability of our results to other rural communities needs to be considered.…”
Section: Discussionsupporting
confidence: 82%
“…To further validate the WHS measure of urbanicity, we examined whether WHS-defined urban areas had higher rates of known transnational indicators of urban living (eg, percentage of jobs in agriculture, household television ownership, and household electricity), confirming that households identified as urban in the WHS conformed to common validated characteristics of urban areas (eTables 4 and 5 in the Supplement). 21 Outcomes: Psychotic Experiences and Psychotic Disorder All participants were asked questions about psychotic symptoms that came from the WHO Composite International Diagnostic Interview (CIDI), version 3.0. 22 The psychosis module…”
Section: Variablesmentioning
confidence: 99%
“…The study population was determined by those individuals with physical activity and sitting time (number of doctors per inhabitant, amount of medical units and access to health services). 12 For each participant, an urbanicity score was given according to their state. Two overall urbanicity indices were computed by summing the seven sub-scores where the Demographic sub-score was measured as population size (Overall urbanicity 1) and as population density (Overall urbanicity 2).…”
Section: Study Populationmentioning
confidence: 99%
“…9 More recently, tools have been developed to provide a more comprehensive measurement of urbanicity, incorporating variables such as economic activity, communications, education, infrastructure and social services. 10,11,12 Features of the built environment such as the perceived proximity to shops and recreational facilities, street connectivity, and aesthetic qualities of a place are positively associated with physical activity. 13,14 A number of studies have also suggested that areas in which buildings are within close proximity to one another, and that facilitate walking between locations, are associated with greater physical activity.…”
Section: Introductionmentioning
confidence: 99%